Corticotroph Hyperplasia and Cushing's Disease - Diagnostic Features and Surgical Management. (16th November 2020) - Catalino, Michael P; Meredith, David; De Girolami, Umberto; Min, Le; Tavakol, Sherwin; Laws, Edward R
Abstract: INTRODUCTION: The histopathology of Cushing's disease is frequently inconsistent, even with biochemical remission. METHODS: This 17-year retrospective cohort study included biochemically confirmed Cushing's disease and associated pathology. Histopathology was confirmed by two experienced neuropathologists and compared with autopsy specimens. Immunohistochemistry was performed using antibodies against ACTH (Dako clone M3501). Covariate associations were explored. Recurrence-free-survival of both groups was compared using a Cox-proportional hazard model. RESULTS: Fifteen hyperplasia and 48 adenoma patients were included. Normal pituitary acinar architecture was highly variable. Hyperplasia was diagnosed based on significantly expanded acini showing retained reticulin architecture and predominant staining for ACTH. In hyperplasia, compared to adenoma, equivocal/diffuse findings on MRI were more common (46% vs 17%; P  = .03), lesion+ (lesion+some normal) removal less frequent (33% vs 65%; P  = .03), nadir cortisol higher (median 9.4[3.6-15.6] vs 2.8[1.4-5.4]; P  = .01), and hours-to-nadir cortisol greater (median 61.5[30-71] vs 27[15-48]; P  = .01). Initial biochemical remission was similar (67% vs 85%;p = 0.11) Median follow-up time was 1.9(0.7-7.6) years for the hyperplasia group and 1.2(0.4-2.4) years for the adenoma group. Nadir cortisol level was the only significant predictor of remission on multivariate analysis (OR 0.28[0.08-0.95]; P  = .04). There was no difference in recurrence-free survival between the groups (p = 0.85). CONCLUSION: Cushing's disease associated with predominant ACTH staining amidst expanded acini with retained architecture supports the diagnosis of corticotroph hyperplasia. Imaging and operative findings can be ambiguous, and thus, compared to typical adenomas with a pseudocapsule, the surgical approach is more nuanced, but biochemical outcomes are no different. Post-operative cortisol dynamics were different, suggesting pathophysiological variation.